Impactos da pandemia no ciclo de alfabetização em uma escola pública da periferia paulistana - Silva, Crislane Santos (2022)
The aim of this research was due to the following issues: How the pledges which are in the legislation for the guarantee of the teaching quality in the beginning levels (literacy) they were done for the Município de São Paulo during the COVID-19 pandemic? Which qualitative policies regarding to the literacy they were implemented during the pandemic for the specific Município? At the searched school, they were succeed in any degree? The tool of this research was the mapping and the analisys of the effectiveness of the quality policies during the pandemic period focusing on the literacy. As the general target, we will analyse the effectiveness of the Public policies Intitution related to the quality education of the literacy, in a school from the Município de São Paulo during the pandemic, taking into account the legislation Applied to this issue. The specific goals were: evaluate the effectiveness and the aplicability of the qualitative policies, analysing their execution at the literacy during the COVID-19 pandemic. Moreover, the other goal was to identify the lessons we gained from this social isolation in which contributed to the improvement of the literacy work. From the point that the Município de São Paulo showed limitation at the reach of the adopted policies in order to assist the students, assuring them the access and the permanence, even though it was online. The research was made at a public elementary school from município de São Paulo and the participants were five literacy teachers, two pedagogical coordinators and a principal and an interview semi- structured. It means a intervention- reseach of qualitative nature with tools of data collection ruled in case-studies at the mentioned school, dialogue with the literacy teachers and the manager employees. And yet, semistructured interviews done to the individuals from this research by means of focal group.We also analysed document and the valid legislation that extent Federal and municipal. The theorical sources of this research were critic authors, pos Marxist, in the area of Education, , such as: Vieira (2007), Ball (2016), Roggero (2021), Moran (2017-2018), Luckesi (2011), Ludke and André (1986), Gatti (2005) and Haddad (2022). After carrying out the empirical research, it was possible to verify that the general objective and the specific objectives were reached, evidencing the instituted and implemented policies in the analyzed school, as well as, what prospered, evidencing the critical moments and the observed contradictions. There was also confirmation of the suggested conjecture. As a proposal, we suggest maintaining the use of technological equipment and the platform, in addition to offering teacher training to continue using the acquired technologies, serving as a support and ally to the literacy process, recovery and strengthening of learning, according to the research agenda presented in the final chapter.